Atividade adjuvante dos óleos de amendoim (Arachis hypogaea L.), algodão (Gossypium hirsutum L.) e arroz (Oryza sativa L.) na resposta imune humoral e celular - Mota, Erika Freitas (2006)
Each molecule or substance that is able to favor or amplify a particular situation in the cascade of immunological events, leading to a better immunological response, can be defined as an adjuvant. The development of new adjuvants is fundamental, because it is now known that adjuvants are critical for determining the magnitude and direction of immune response by mechanisms including increased antigen presentation, uptake, distribution and selective targeting. In the present study, we investigated the adjuvant effect of cottonseed, peanut and rice oils. The immuneadjuvant activity was evaluated in relation to the synthesis of specific serum antibodies and the delayed-type hypersensitivity (DTH) both induced by the immunization of Swiss albino mice with ovalbumin, separately, as well as associated to the emulsion of plant oils and the classical adjuvants, Freund complete adjuvant (FCA) and aluminum hydroxide (ALUM); to the capacity of protect against murine experimental leishmaniasis after vaccination and to the pro-inflammatory activity in subcutaneous air-pouch, including the induction of production of nitric oxide and hydrogen peroxide and exudation of proteins. The cottonseed, peanut and rice oils presented differentiated adjuvant effect in humoral and cellular immune response and a potential inflammatory effect, they are able of induced leukocytes migration, production of nitric oxide and hydrogen peroxide. Furthermore, these oils stimulated a poor OVA-specific IgE response. The peanut oil, whose stability of the emulsion is low and presents non phenolic antioxidant compounds, was able to stimulate the synthesis of anti-ovalbumin antibodies in the primary humoral immune response (HIR). However, it did not enhance the cellular immune response (CIMR) and in the case of vaccination against cutaneous leishmaniasis, the protective response provided by the antigen alone was suppressed. The rice oil, which have a good stability of the emulsion and presents antioxidant compounds (phenolic and non phenolic), exhibited the biggest adjuvant capacity in the CIMR for DTH reaction and to allow for the protection against murine cutaneous leishmaniasis. Also, it has only favored the synthesis of antibodies after the second booster. The cottonseed oil was a good adjuvant in the secondary HIR. It has presented a more intense response than the stimulated for the CFA, presenting a strong adjuvant potential. Further, it was able to favor the DTH reaction. This variety of induced/modulated immune response by vegetable oil emulsions seems to be a differential compared to other adjuvant in use and makes possible the use of these oils as tools for the study of kinetic of antibodies synthesis and the use in different procedures of immunization. It still worth mentioning, the fact that vegetable oils be biodegradable, cheap, easily acquired and safe.